从关联理论看字幕中文化词的翻译 ：以电影《指环王》三部曲为例 = Subtitle translation of cultural references from the perspective of relevance theory : a case study of The Lord of the Rings - 黄佳娴 Wong, Jia Xian (2018)
文化词是字幕翻译中常受到关注的一大议题，因为译者不但需要了解两种截然不同的文化，还需要在影视翻译的时间与空间限制下，传递文化词在语言之外的信息。本研究以《指环王》（The Lord of the Ring；《魔戒》）为案例，从关联理论视角分析电影字幕中英语文化词的汉译策略，通过比较两种不同源流（官方与网络字幕组）的字幕版本，以期能够全面探讨字幕中文化词翻译的现象。 从关联理论来看，字幕翻译可视为是一种译文与目标语观众之间的语言交际。《指环王》电影建构起托尔金笔下的架空世界（Secondary World），字幕中出现了许多与中土世界（Middle Earth）有关的地理环境、民族、和社会政治的文化词汇。本研究发现，在两种字幕中，网络字幕组的译本倾向于呈现源语文化词完整的含义，主要以音译与补偿的翻译策略，提供目标语观众最大的信息量去理解原文。相较之下，官方版本则以目标语观众的认知力为基础，通过删减、转移、替换和概括策略，选择能够达到最佳关联的译文，让观众不费余力就能明白原文。从关联理论来看，若要让汉语文化背景的目标语观众轻松理解这些出现在虚构世界中的文化词，则翻译应达到最佳关联（Optimal Relevance）和制造语境效果（Contextual Effect）。制造语境效果是从强化认知关联开始，强化认知关联的现象并不是网络字幕组倾向的提供最大信息量，而是选取与观众有最佳关联的译文。 同时，本文也证明了关联理论要求译者对观众的动态语境进行推理，有助于维系字幕与影视作品中其他视觉、声音元素之间的关联性，让观众更容易理解字幕中文化词的翻译，获得与源语观众相似的语境效果。 This study investigates the dominant strategies of translating cultural references from English to Chinese (Simplified) adopted by the translators from two different subtitle groups of the English fantasy movies The Lord of the Ring Trilogy: the official version published by Netflix and the internet version by Zhong tu hong pi shu （中土红皮书）subtitle group. It also discusses the implications of these strategies from a relevance-theoretic perspective. To translate the cultural references in a subtitled film, the subtitler needs to understand two diverse cultures and convey the meanings outside of the language under the time and space constraints inherent in the subtitling process. Under the guidance of relevance theory, the subtitler should render the culture references based on his belief of what is relevant to target readers and achieve optimal relevance and create an adequate contextual effect. The study reveals that the dominant strategies of transposition, substitution and generalization from official version (Netflix, subtitle 1) is geared to the achievement of optimal relevance and contextual effect while the version of amateur subtitle group (Zhong tu hong pi shu, subtitle 2) is more limited in processing the information of source text and aims to provide the target audiences with the “optimal information”. It also demonstrates when the translator takes the audience’s dynamic context into account, the subtitles are more relevant to the other visual or audio elements in the film. Therefore, the target audiences tend to have a better understanding to the translation of cultural references and achieve the similar contextual effects as the source culture audiences.